2013
DOI: 10.1111/aji.12095
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Contraceptive Efficacy of Escherichia coli‐Expressed Recombinant Porcine Zona Pellucida Proteins

Abstract: Availability of recombinant porcine proteins will be useful in the development of contraceptive vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 43 publications
1
34
1
Order By: Relevance
“…Other studies on white-tailed deer and feral horses have reported that treatment with ZP vaccines does not affect time budget, social behaviour and body condition (Miller et al 2001;Hernandez et al 2006;Ransom et al 2010). The incidence of ovarian pathologies was significantly reduced when purified PZP proteins were used in vaccine constructs (Gupta et al 2013).…”
Section: Immunocontraceptive Vaccinesmentioning
confidence: 88%
See 2 more Smart Citations
“…Other studies on white-tailed deer and feral horses have reported that treatment with ZP vaccines does not affect time budget, social behaviour and body condition (Miller et al 2001;Hernandez et al 2006;Ransom et al 2010). The incidence of ovarian pathologies was significantly reduced when purified PZP proteins were used in vaccine constructs (Gupta et al 2013).…”
Section: Immunocontraceptive Vaccinesmentioning
confidence: 88%
“…Porcine ZP (PZP) immunocontraceptive vaccines, derived from ZP isolated from pig ovaries, have been effective in many ungulate species, monkeys, seals, bears and marsupials, but not in rodents, cats, dogs and wild pigs (Eade et al 2009;Kitchener et al 2009;Kirkpatrick et al 2009Kirkpatrick et al , 2011 McLaughlin and Aitken 2011; Table 1). However, recently formulated recombinant PZP3 and PZP4 vaccines, delivered in three injectable doses, caused infertility in up to 89% mice, depending on the formulation type (Gupta et al 2013).…”
Section: Immunocontraceptive Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunization of female mice with E. coliexpressed recombinant porcine ZP3 and ZP4 with or without promiscuous T cell epitopes of either TT or bovine RNase led to the generation of high antibody titers with concomitant decrease in fertility. 109 In general, fusion proteins with promiscuous T cell epitopes generated higher antibody titers as well as contraceptive efficacy as compared with recombinant porcine ZP3 and ZP4 without promiscuous T cell epitope. The litter size in the immunized animals was significantly decreased as compared with the control group.…”
Section: Potential Of Recombinant Zp Proteins For Inhibiting Fertilitymentioning
confidence: 93%
“…The litter size in the immunized animals was significantly decreased as compared with the control group. 109 Immunization of female marmoset (Callithrix jacchus) with the recombinant human ZP3 expressed in Chinese Hamster Ovary (CHO) cells induced long-term infertility. 110 Immunized animals showed ovarian pathology associated with the depletion of primordial follicles.…”
Section: Potential Of Recombinant Zp Proteins For Inhibiting Fertilitymentioning
confidence: 99%